Aloysius Archer : Dream Town - Book 3 - Baldacci, David (New York : Grand Central Publishing, 2024)
"Private Investigator and ex-World War II veteran Aloysius Archer heads to Los Angeles, the city where dreams are made and shattered, and is ensnared in a lethal case."--
Keywords: Archer, Aloysius -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Ex-convicts -- Fiction; Veterans -- Fiction; Murder -- Investigation; Fiction; California -- Fiction; Detective and mystery fiction; Thrillers (Fiction)